PEMETAAN GEOHIDROLOGI DAERAH DONOROJO KABUPATEN PACITAN - Prayogo, Teguh (Jurnal Teknologi Lingkungan, 2009)
Water is a component in the earth that is very important for human life. The availabilityof water is always wanted to meet a demand of water supply, such as for drinkingwater, washing, taking a bath, and etc. Along with population growth, so the need ofwater will be still increasing, including Tanah Datar. In this paper will be describedconcerning to characteristics, and condition of water in Pacitan Area, East JavaProvince, especially Donorojo district. This location occupies geographically betweenthe latitude of 00o17’ and 00o39’ south and the longitude of 100o19’ and 100o51’ eastBased on survey in field, condition of aquifer in Telaga Banta is located in 20 – 60meter depth, and the result of laboratory points to that the quality of water in thisarea meets the requirement for drinking water.The main uses of ground water include irrigation uses, drinking-water and otherpublic uses, and for supplying domestic water to people who do not receive publicsupply water. The majority of water used for self-supplied domestic and livestockpurposes came from ground-water sources.